Dynamic display of spatial data-reliability: Does it benefit the map user? - Evans, Beverley J. (Computers & geosciences, 1997)
As users of maps we are dependent upon their veracity and by extension the reliability of the data they contain. Several research projects have explored possible methods of visually representing data certainty, a kind of metadata; methods considered include depicting the metadata as a map that is separate from the data map, imbedding the metadata into the data map, and creating an interactive environment allowing simultaneous viewing of both data and metadata. A practical consideration, as we develop methods for graphic depiction of data reliability, is the reaction to and acceptance of proposed methods by the map user. This research studied how maps containing graphically depicted reliability information are used. Potential “usability” of the cartographic display of data reliability is explored by the type of map user (novices versus experts, and males versus females) and the type of map use (assessment of map reliability, confidence in data reliability assessments, and ability to judge the proportion of the areas within the map containing highly reliable data). This study addressed these issues by exploring and analyzing subject responses to an interactive cartographic display of data and its level of reliability. The graphic depiction of reliability information was found to be accessible and comprehensible by all subjects; novice or expert, and male or female. Two methods of combining data and reliability information, as a composite static display and as an animation, were both found to be helpful by the subjects tested. Two other methods of obtaining reliability information, a map displaying only reliability information and an interactive “toggling” between the data and reliability information were not found to be as efficient or effective as the combination methods.